Government concerns of consumers’ intention to purchase green products (preliminary study-Malaysia evidence) - Nezakati, Hossein; Hosseinpour, Masoumeh; Hassan, Mazlan (Asian Network for Scientific Information, 2014)
Facing with the environmental degradation, the Malaysian government as well as other parts of the world takes the path of protecting the environment. Along with this way, the government encourages the public to perform green behaviour. For instance, in the market, different types of green or environmentally friendly products are prepared for the desirable consumers. The main objective of this study as a preliminary one is to find out the latent factors that can affect the intention of respondents to purchase green products. Second, it aims to determine to which the selected socio-economic characteristics and attitudinal factors influence the respondents= intention to purchase green products.